(untitled) (International Journal of Engineering and Computer Science, 2016)
For data transmission in wireless sensor networks (WSNs), routing is the main course. Many routing algorithm have been proposed for effective data transmission. For data transmission, dynamic cluster selection is necessary to create in the network. Dynamic cluster selection is performed based on energy level of node. Node with higher energy becomes cluster head, after cluster head node is selected; cluster head collects the data from every member of the cluster and forwards that to base station. Cluster head is rotated based on energy level. Proposed mechanism confirms data transmitted effectively and energy efficiency of the node increase. It is implemented using simulator NS2.34 along with TCL script.